Market as a Sequence of Exchanges between Organizational Fields - РадаевВадим Валерьевич (Journal of Economic Sociology, 2010)
The paper suggests a theoretical concept of the market as intersection of two separate notions. The first notion of organizational field is borrowed from the new economic sociology. The second notion of supply chain is developed in marketing science. In sum, the market is presented as a chain of subsequent exchanges carried out by buyers and sellers from closely related organizational fields. Elaborating this understanding of the market, the author treats the market exchange as a social process in which economic transactions densely interweave with power relations. Transaction is the core element of any kind of market exchange. At the same time, the conclusion of a transaction between firms is originated from complex compromises, reflecting interactions and negotiation concerning the terms of market exchange. The author singles out three components of negotiated exchange: (1) complex exchange objects; (2) multiple dimensions of the exchange, and (3) motivation structure of economic actors participating in exchange relationships. Thus, market exchange could be arrayed as a part of more comprehensive social exchange. Along with this statement, market exchange is embedded into power relationships. Market actor’s bargaining power is based on his authority which permits him to control competitor’s actions. The paper supplies conceptual ideas and tools for sociology of markets. At the same time, its insights largely were originated from the numerous empirical studies on Russian retailing.